VITILIGO CAUSES, SYMPTOMS, TREATMENT AND PREVENTION - Shukurova Barchinoy Abdulhofiz qizi; Pardayev Muhayyo Chori qizi; Turdiyeva E’zoza Mamatrayim qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Vitiligo-currently,polutology is considered as a disease that occurs due to the disruption of various internal organs and systems. The causes of the disease on the territory of Uzbekistan are diseases of the liver, gall bladder, thyroid gland, gastrointestinal diseases, more parasites in children, anemia in women and chronic diseases of various intestines and genitals. We will learn more about vitiligo disease in this article.